The Brand Image Influence on the Relationship Between Social Media Advertising and Sustainable Tourism Practices in Petra (Jordan) - Alfdool Sabri Mahmoud; Teruel-Serrano María Dolores; Alonso-Monasterio Pau (ECONOMICS)
This study aims to establish the mediating role of brand image, including advertising and promotion content distributed on social media platforms, which can improve positive brand image in the relationship between social media advertising and sustainable tourism practices at Petra in Jordan. This study survey contained 332 of the participant’s respondents who visited Petra from different countries. | A structured questionnaire was also embraced to gather primary data. The data were analyzed utilizing Smart-PLS, which was used to classify the measurement and structural models. The mediating influence of together social media advertising and sustainable tourism practices was tested too. The outcomes showed that brand image positively mediates the link between social media advertising and sustainable tourism practices at Petra. For that reason, it can be supposed that brand image among tourists who visit Petra plays a crucial role in promoting social media advertising for improved sustainable tourism practices at Petra. Finally, this study delivers an empirical indication of a phenomenon not studied at Petra in Jordan where the tourists who visited Petra concreted in norms and customs for sustainable tourism practices. The outcomes underline the significance of brand image in mediating the link between social media advertising and sustainable tourism practices at Petra.